2002
DOI: 10.1074/jbc.m204136200
|View full text |Cite
|
Sign up to set email alerts
|

The PDZ Binding Motif of the β1 Adrenergic Receptor Modulates Receptor Trafficking and Signaling in Cardiac Myocytes

Abstract: ␤ 1 and ␤ 2 adrenergic receptors (AR) regulate the intrinsic contraction rate in neonatal mouse cardiac myocytes through distinct signaling pathways. It has been shown that stimulation of ␤ 1 ARs leads to a protein kinase A-dependent increase in contraction rate. In contrast, stimulation of ␤ 2 ARs has a biphasic effect on contraction rate, with an initial protein kinase A-independent increase followed by a sustained decrease that is blocked by pertussis toxin. The ␤ 2 AR undergoes agonist-induced endocytosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
104
2
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(116 citation statements)
references
References 33 publications
4
104
2
1
Order By: Relevance
“…4). These results in mouse cardiac myocytes are unlike those reported in another study, which have implied that the WT ␤ 1 -AR did not internalize in mouse cardiac myocytes in response to isoproterenol (45). Our results clearly showed that the ␤ 1 -AR was efficiently trafficked in mouse cardiac myocytes.…”
Section: Discussioncontrasting
confidence: 57%
“…4). These results in mouse cardiac myocytes are unlike those reported in another study, which have implied that the WT ␤ 1 -AR did not internalize in mouse cardiac myocytes in response to isoproterenol (45). Our results clearly showed that the ␤ 1 -AR was efficiently trafficked in mouse cardiac myocytes.…”
Section: Discussioncontrasting
confidence: 57%
“…␤ 1 AR has no tyrosine residues in its C-tail but does terminate in a PDZ binding motif (ESKV) that is recognized by PSD-95 and MAGI-2, two postsynaptic scaffolding proteins that respectively inhibit and enhance receptor internalization (48,49). Mutation of the PDZ motif of mouse ␤ 1 AR enhances agonist-mediated endocytosis in mouse cardiac myocytes (50). When we used chimeric receptors in which the C-tails had been exchanged, we found that upon persistent agonist stimulation, ␤ 2 /␤ 1 ct-AR underwent up-regulation, and ␤ 1 /␤ 2 ct-AR underwent down-regulation, the order of down-regulation being ␤ 2 AR Ͼ ␤ 1 /␤ 2 ct-AR Ͼ Ͼ ␤ 2 /␤ 1 ct-AR Ͼ ␤ 1 AR.…”
Section: Discussionmentioning
confidence: 99%
“…In neonatal cardiac myocytes from β 1 and β 2 receptor double knockout mice, dual coupling of the β 3 subtype to both G s and G i , with the G i component dominating, has been described (Devic et al 2001). These specific signaling properties of β receptor subtypes have been linked to subtype-selective association with intracellular scaffolding and signaling proteins, and distinct subcellular localization (Steinberg 1999, Hall and Lefkowitz 2002, Xiang et al 2002, Xiang and Kobilka 2003a. Figure 3A is a schematic representation of β-adrenergic receptor signaling in the heart.…”
Section: The Cardiac β-Adrenergic Pathwaymentioning
confidence: 99%